Family therapy for an Internet‐addicted young adult with interpersonal problems. Issue 4 (November 2014) - Park, Tai Young; Kim, Sunhee; Lee, Jieha
<x xml:space="preserve">Abstract</x> This qualitative case study examined the effectiveness of treating an Internet‐addicted young adult suffering from interpersonal problems based on the Mental Research Institute (MRI) interactional model and Murray Bowen's family systems theory. We analysed the data with a consistent comparative analysis method as well as utilizing Miles and Huberman's matrix and network. We determined that the characteristics of the parents' family of origin and dysfunctional communication pattern were factors associated with the interpersonal problems revealed by the Internet‐addicted young adult. Factors that influenced problem‐solving consisted of the awareness of the relationship between the family of origin and presenting problems, improved communication among family members and overcoming the young adult's resistance. The findings of this study reveal that both the MRI model and Bowen's family systems theory were effective treatments for an Internet‐addicted young adult with interpersonal problems. Practitioner points An extensive analysis of family‐of‐origin problems and communication patterns might be beneficial in treating an Internet‐addicted young adult with interpersonal problems. Treatment outcomes will be enhanced if the therapist is aware of the relationship between the family of origin and the nuclear family. Functional and sincere conversation between parent and child is imperative to ameliorate risks involved with Internet addiction.